Risk factors of osimertinib-related cardiotoxicity in non-small cell lung cancer - Wang, Yunlong; Deng, Xuan; Qiu, Qinggui; Wan, Mengchao (Frontiers in Oncology, 2024)
Objective To investigate the risk factors associated with cardiotoxicity in patients with non-small cell lung cancer (NSCLC) treated with osimertinib. Methods A total of 268 patients with NSCLC treated with osimertinib in our hospital from June 2019 to December 2023 were selected to observe the occurrence of cardiotoxicity and were divided into cardiotoxicity group and non-cardiotoxicity group. The differences in age, gender, body mass index (BMI), smoking, alcohol consumption, tumor stage, hypertension, diabetes, hyperlipidemia, chemotherapy, radiotherapy, antiangiogenic drugs, and osimertinib treatment time were recorded and analyzed. Logistic regression was used to analyze the risk factors for cardiotoxicity in patients with non-small cell lung cancer caused by osimertinib treatment. Results Among the 268 patients with NSCLC treated with osimertinib, 58 patients developed cardiotoxicity, and the incidence of cardiotoxicity was 21.64%. There were statistically significant differences between the cardiotoxicity group and the non-cardiotoxicity group in terms of smoking history, hyperlipidemia history, combined chemotherapy, and combined radiotherapy (P < 0.05). Further analysis showed that patients with a smoking history were at increased risk of cardiotoxicity compared with non-smoking patients (OR = 2.569, 95% CI = 1.398–6.523). Patients with hyperlipidemia were at increased risk of cardiotoxicity compared with those without hyperlipidemia (OR = 3.412, 95% CI = 2.539–7.628). Patients with chemotherapy were at increased risk of cardiotoxicity compared with those without combination chemotherapy (OR = 2.018, 95% CI = 1.426–4.517). Patients undergoing radiotherapy to the left chest were at increased risk of cardiotoxicity compared with those without combined radiotherapy (OR = 1.629, 95% CI = 1.273–4.206). Conclusion The incidence of cardiotoxicity in patients with NSCLC is high due to osimertinib treatment. A history of smoking, hyperlipidemia, combination chemotherapy, and radiotherapy to the left chest are independent risk factors for cardiotoxicity in patients with NSCLC treated with osimertinib.